Effect of pruning operation and nutrition on fruit yield and quality of litchi (Litchi chinensis) - KUMAR, RAJESH (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out by National Research Centre on Litchi, Muzaffarpur, Bihar at farmers field for two years during 2008-09 and 2009-10 in an orchard having 18 years old litchi (Litchi chinensis Sonn.) plantation of cv Shahi spaced at 10 m × 10 m have shown the significant need of pruning operation and proper nutrition in commercial bearing litchi trees, which must maintain control of both tree size and fruit productivity. The types of pruning, i.e. Selective pruning to frame semicircular canopy shape and pruning to centre open the canopy with nutrition including recommended dose of fertilizers (RDF) application have been found to give significant effect on plant height, canopy volume (m3), shoot length, shoots with bearing panicle, initial fruit set (no./panicle) and fruit yield as well as fruit weight at both treatment level and their interaction effect. Among the various treatments, selective pruning (65.65 kg/plant; 86.35 kg/plant) and nutrient application in recommended dose (60.48 kg/plant; 67.35 kg/plant) resulted in highest fruit production during both the years and their interaction effect was also found to be significant. In both the years, fruit yield increased with types of pruning system and nutrition. During the end of the experimentation, the initial and after soil test analysis for physicochemical properties showed the appreciable increase in the soil organic matter and the NPK availability status improving the soil physical properties.